CHALLENGES TO THE BRAZILIAN AGROFOOD INDUSTRY IN THE GLOBAL MARKET - de Paula, Nilson M. (Revista de Economia, 2001)
A globalização da economia mundial vem sendo amplamente discutida, revolvendo um debate tanto teórico quanto ideológico a respeito dessa multifacetada transformação, com a qual todos os países vem se envolvendo. Independente dos rumos dessa discussão, a questão da competitividade tem se tornado essencial nas relações econômicas internacionais da última década, quando a maioria dos países começaram a promover uma abertura tanto aos fluxos de investimento quanto de comércio. Abstract Globalization has been deeply discussed revolving around a theoretical and ideological contention concerning this many-sided transformation with which, in one way or another, all countries have become entangled. Whatever the course of the discussion, competitiveness has become the key question in the international economic relations of the last decade, when most countries started opening up their economies to the external flows of trade and investment. The core of this analysis indicates the challenges facing Brazil in the international market when differentiated products appear to dominate trade relation. The discussion explores the extent to which foreign direct investment can change the conditions under which the country can boost its international competitiveness. As it will be argued here, the process of opening up the Brazilian economy in the 1990s has so far only consolidated the countrys position as a commodity exporter, whereas the mainstream of the international market has consisted of processed and differentiated products.